Exploring The Use Of Tiktok Educational Video To Increase Students’ Vocabulary At SMKN 02 Batu - Lutfi Rasyidah Amelia; Sugeng Susilo Adi (PT Publikasiku Academic Solution, 2024)
Vocabulary is essential for English learners to understand the material. To increase students' interest in learning new words, medias can be used. This study aims to evaluate the practicability of TikTok as an EFL educational platform based on students' perceptions and assist educators in this regard. This study employs a qualitative method using a questionnaire and interviews to determine the number of TikTok users and to gather information from interviewees to provide a comprehensive description and elucidate the perceptions of students. Purposive sampling was used to select 27 students majoring in Agricultural Product Processing Agribusiness from SMKN 02 BATU, of which 5 were chosen for interviews. The interview session identified five themes related to students' perception of TikTok educational videos and their impact on vocabulary development: 1) content type, 2) benefits, 3) advantages, 4) weaknesses, and 5) impacts. The results revealed that students mostly learn new vocabulary effectively through TikTok since it provides a practical way to understand the meaning through real-life examples from TikTok. The study found that using media to teach English to vocational students is more effective than using textbooks, despite some students finding it distracting. This suggests that implementing TikTok educational videos in the future could be more effective than previous methods.